Prediction of a weakly bound excited state in the He-4(2)-Li-7 molecule - Delfino, A.; Frederico, T.; Tomio, L. (American Institute of Physics (AIP), 2000)
A scale-independent approach, valid for weakly bound three-body systems, is used to analyze the existence of excited Thomas-Efimov states in molecular systems with three atoms: a helium dimer together with isotopes of lithium (Li-6 and Li-7) and sodium (Na-23). With the present study and the available data, we can clearly predict that the He-4(2)-Li-7 system supports an excited state with binding energy close to 2.31 mK. (C) 2000 American Institute of Physics. [S0021-9606(00)30442-1].